2021
DOI: 10.1111/jrh.12604
|View full text |Cite
|
Sign up to set email alerts
|

The association between hospital care transition planning and timely primary care follow‐up

Abstract: Purpose To determine whether Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) Care Transitions (CTM‐3) Scores were associated with timely (14‐day) primary care provider (PCP) follow‐up visits, and to look for disparities across various types of urban and rural hospitals. Methods Data were obtained for 3,299 hospitals: 2,000 urban, 544 micropolitan prospective payment system (PPS), 109 micropolitan critical access hospital (CAH), 252 noncore rural PPS, and 394 noncore rural CAH. HCAPPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Utilizaram medicações vasoativas 83 (27,7%) pacientes, e método dialítico, 15 (5%). A mediana de tempo de permanência no hospital foi de 13 dias (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Apenas 10 (3,3%) pacientes reinternaram em até 30 dias após a alta.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Utilizaram medicações vasoativas 83 (27,7%) pacientes, e método dialítico, 15 (5%). A mediana de tempo de permanência no hospital foi de 13 dias (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Apenas 10 (3,3%) pacientes reinternaram em até 30 dias após a alta.…”
Section: Resultsunclassified
“…Neste estudo, observou-se que aqueles com consulta no hospital pós-alta tiveram melhor percepção da qualidade da transição do cuidado. Outra investigação constatou que escores mais altos de transição de cuidado eram associados a taxas mais altas de consulta de acompanhamento na atenção primária (26) . Diante disso, apesar de inúmeras dificuldades para realizar o acompanhamento pós-alta, reconhece-se que o seguimento por meio de contato telefônico, visita domiciliar e/ou consulta na atenção primária pode evitar a readmissão hospitalar e o atendimento em serviços de emergência (27,28) .…”
Section: Discussionunclassified
“…In this study, it was observed that those with a hospital appointment after discharge had a better perception of care transition quality. Another investigation found that higher care transition scores were associated with higher rates of follow-up appointment in primary care (26) . Therefore, despite numerous difficulties in carrying out post-discharge follow-up, it is recognized that follow-up through telephone contact, home visits and/or appointment in primary care can avoid hospital readmission and emergency care (27,28) .…”
Section: Discussionmentioning
confidence: 99%